2021
DOI: 10.3390/cells10092487
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin-Promoted Caveolin-1 Overexpression Maintains Mitochondrial Morphology and Function in PSAPP Alzheimer’s Disease Mice

Abstract: Mitochondrial dysfunction plays a pivotal role in the Alzheimer’s Disease (AD) pathology. Disrupted mitochondrial dynamics (i.e., fusion/fission balance), which are essential for normal mitochondria structure and function, are documented in AD. Caveolin-1 (Cav-1), a membrane/lipid raft (MLR) scaffolding protein regulates metabolic pathways in several different cell types such as hepatocytes and cancer cells. Previously, we have shown decreased expression of Cav-1 in the hippocampus of 9-month (m) old PSAPP mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Mitochondria fission is a basic and vital process via programmed and sequential membrane movement that (Mahaman et al, 2022 ) involves healthy mitochondria fragments for growing physiological requirements; (2020) aged or damaged mitochondria divided into healthy mitochondria for recycling and pre-degraded mitochondria for clearance (Wolf et al, 2020 ; Luan et al, 2021 ). Impaired mitochondrial dynamics is widely established in AD model mice and cells, as well as AD individuals (Manczak et al, 2011 ; Reddy et al, 2011 , 2018 ; Manczak and Reddy, 2012a ; Zhu et al, 2013 ; Kandimalla et al, 2021 ), as determined by the lower expression of mitochondrial fission genes ( DRP1 and FIS1 ) and higher phosphorylation level of dynamin-related protein1 (DRP1), leading to reductive mitochondria fragmentation and neuronal energy dysfunction (Reddy et al, 2011 ; Manczak and Reddy, 2012a ; Misrani et al, 2021 ; Wang et al, 2021a ; Dhapola et al, 2022 ). Incidentally, additional studies indicate that decreased DRP1 promotes cognitive performance and improves mitophagy and dendritic spines in tau-transgenic mouse model and APP/PS1 mice (Kandimalla et al, 2021 ; Misrani et al, 2021 ; Song et al, 2021 ), in which DRP1 is overactivated under abnormal conditions; and consistently, various DRP1 inhibitors promote fusion and improve cognition in AD (Dhapola et al, 2022 ).…”
Section: Apoe4 and Mitophagy-specific Processes In Admentioning
confidence: 99%
“…Mitochondria fission is a basic and vital process via programmed and sequential membrane movement that (Mahaman et al, 2022 ) involves healthy mitochondria fragments for growing physiological requirements; (2020) aged or damaged mitochondria divided into healthy mitochondria for recycling and pre-degraded mitochondria for clearance (Wolf et al, 2020 ; Luan et al, 2021 ). Impaired mitochondrial dynamics is widely established in AD model mice and cells, as well as AD individuals (Manczak et al, 2011 ; Reddy et al, 2011 , 2018 ; Manczak and Reddy, 2012a ; Zhu et al, 2013 ; Kandimalla et al, 2021 ), as determined by the lower expression of mitochondrial fission genes ( DRP1 and FIS1 ) and higher phosphorylation level of dynamin-related protein1 (DRP1), leading to reductive mitochondria fragmentation and neuronal energy dysfunction (Reddy et al, 2011 ; Manczak and Reddy, 2012a ; Misrani et al, 2021 ; Wang et al, 2021a ; Dhapola et al, 2022 ). Incidentally, additional studies indicate that decreased DRP1 promotes cognitive performance and improves mitophagy and dendritic spines in tau-transgenic mouse model and APP/PS1 mice (Kandimalla et al, 2021 ; Misrani et al, 2021 ; Song et al, 2021 ), in which DRP1 is overactivated under abnormal conditions; and consistently, various DRP1 inhibitors promote fusion and improve cognition in AD (Dhapola et al, 2022 ).…”
Section: Apoe4 and Mitophagy-specific Processes In Admentioning
confidence: 99%
“…In the AD brain, both clinical and preclinical evidence has shown disrupted mitochondrial dynamics, including excessive fission and decreased fusion activity. This imbalanced dynamic change will result in failure of clearance of the damaged mitochondria and impaired axonal mitochondrial transport and exacerbate mitochondrial DNA (mtDNA) changes (Hirai et al, 2001;Manczak et al, 2018;Pickett et al, 2018;Wang et al, 2021a). The present study revealed a significant decrease in hippocampal MFN2 accompanied by a wide range of mitochondrial alterations from early-stage (6-m) APPKI mice.…”
Section: Discussionmentioning
confidence: 55%
“…A separate cohort of 3-m APPKI mice were used in this experiment. Mice were euthanized, and hippocampi were collected and processed immediately on ice for mitochondrial function assessment (Kilbaugh et al, 2015;Wang et al, 2021a). An Oroboros O2k respirometer was used to assess oxygen consumption rate.…”
Section: High-resolution Mitochondrial Respirometrymentioning
confidence: 99%
“…It regulates the integrity of neurons and plays a fundamental role for synaptic and neuroplasticity. Recent researches have demonstrated that decreased Cav-1 is significantly related to AD progression and promoted Cav-1 level by transgenic manner in hippocampus effectively ameliorated the cognitive performance of AD mice (Wang et al 2021 ). In the present study, we found that the level of Cav-1 in the hippocampus of AD mice was upregulated after Ca treatment, whereas significantly downregulated upon miR-138-5p knockdown, suggesting Ca may also mediate AD progression though miR-138-5p/Cav-1 axis.…”
Section: Discussionmentioning
confidence: 99%